Return on Investment With Industrial Perspective: How ROI Perception and ROI Calculating Model Can be Improved in Fast Moving Consumer Goods Industry - Saha, Gautam (Indian Journal of Marketing, 2004)
When a businessman invests some money in a business, he always estimates before an investment what amount of money he can earn from his business or he calculates what amount of money he has earned after some period of time from his investment. This estimation or calculation is simply called Return On Investment shortly ROI. Three categories of ROI are 1) Return on Assets 2) Return On Capital Employed 3) Return on Shareholders Equity are explained below.